PENGENTASAN KEMISKINAN DI ARAS LOKAL (Studi Kasus di Desa Rutong dan Desa Leahari, Kecamatan Leitimor Selatan Kota Ambon, Provinsi Maluku) - Simon Pieter Soegijono (JURNAL MANAJEMEN, 2014)
There was a lot of study about the proverty phenomenon of society. Most of them aim at proverty character and to observe poor people’s eforts as individual or society group to fulfil their life needs, and their capability to survive as well. In case, proverty problem became important notice of stake holders, include government and non government organization. It also considered from all perspective, like social, economy dan culture for decreasing the amount of poor people. At the very least, it done by qualitative approach with study case, can reveal the proverty problem. This research is done at Rutong and Leahari villages, subdistrict Leitimur Selatan Ambon city. Key words: motivation, social capital, survival strategy